Gugma kabug-usan sang kabuhi an analysis of the community-based herbal medicine program in Barrio Obrero, Iloilo City. - Martizano, Reste Marion Fuentes
This qualitative study discusses the historical development of Gugma Kabug-usan Sang Kabuhi - Herbal Medicine Program in Barrio Obrero, Iloilo City based on primary sources. Specifically, it looks like into the manner by which the program was implemented and how its beneficiaries were organized. It also analyzes the results of the program to socio-economic conditions of its members and the promotion of good health in the community., The study also describes and analyzes the Herbal Medicine Program of the Gugma Kabugusan Sang Kabuhi as a community-based alternative medicine program. This entails an in depth analysis of the program's role and impact on the lives of its members and also to the people in Barrio Obrero, Iloilo City. The researcher likewise determined the process of how the program evolved and the experiences of the NGO that started the program. Utilizing in-depth interview, key-informant interview, and Focus Group Discussions as data gathering methods, this study tackles the following objectives: (1) to discuss the historical background that led to the establishment of Gugma Kabugusan Sang Kabuhi Incorporated; (2) to describe the organizational structure, vision, mission and objectives of the Gugma Kabugusan Sang Kabuhi Incorporated as a community-based herbal medicine program and the community organizing process they undergone to establish a people's organization in the community of Barrio Obrero; (3) to identify and discuss the socio-economic benefits derived by members from the program; and (4) to determine the program's impact in the community in promoting community health through a community-led process. The result of the study reveals that Gugma Kabug-usan Sang Kabuhi Incorporated (GKKI) is rooted in the principles of the Health program organized by Assumption Socio Educational Center (ASEC) of Barrio Obrero Iloilo, City. The program started as a small household prayer group in 1975 called Alay Kapwa. Because of the community health problems arise and discussed in the household prayer meetings, Sister Rosalina Ladrido and Belle Eusuya of ASEC (Assumption Socio-Eduational Center) assembled the household groups in 1977 and organized them into a Community-based Health Program (CBHP) enabling them to promote community health through a community -led process. In order to fully surrender the program to the people of Barrio Obrero, the CBHP core group called Volunteer Health Workers became a SEC registered Organization in 1992 and was named as Gugma Kabug-usan Sang Kabuhi Incorporated; a people's organization empowered to continue the works of the CBHP of ASEC. In order to give direction to their programs, the organization formulated their vision, mission and goals with the guidance of ASEC. The organization's mission is to make a self reliant community; their vision is to make families stand on their feet; and their goal is to make 90 percent of the families in their community self reliant. Moreover, the present structure of the organization only presented three distinct positions in the organization; one is the chairperson who oversees all the activities and two is the secretary who functions as a record keeper and treasurer of the organization, and the members who serves as the key builder and implementer of the program. Base on the responses of the participants in the study, the researcher found out four wellness dimensions that greatly describe the impacts of the program in its members. And these dimensions are: Physical Wellness, Mental-Intellectual Wellness, Social-Relational Wellness, and Spiritual Wellness. Moreover, the program also made impacts on the community of Barrio Obrero. The researcher also found out four wellness dimensions that greatly touched the community and these dimensions are; Physical Wellness, Social Wellness, Environmental Wellness, and Spiritual Wellness. The Gugma Kabug-usan Sang kabuhi Incorporated was a successful organization in promoting a community-led process for the effective promotion of the Herbal Medicine Program. The GKKI was the product of a community-led strategy initiated by the Community Based Health Program of ASEC that enabled them to be an effective health-driven People's Organization of Barrio Obrero. Thus, the community-led program started by the CBHP has evolved into a People's Organization giving the people a sense of ownership of the program and a role to continue the works and principles of the CBHP in promoting community health.